Pengaruh Penggunaan Alat Komunikasi Terhadap Kelainan Refraksi Miopia Di Puskesmas Ulak Karang Kota Padang - Amir, Amril; Saunir , Ihsan (CV. ITTC INDONESIA, 2024)
This scientific paper discusses the influence of the use of communication tools on myopia refractive disorders at the Ulak Karang Community Health Center, Padang City. This study aims to find out: (1) whether there is an influence of gadget use on myopia refractive errors at the Ulak Karang Community Health Center in the city of Padang. (2) determine the factors causing the use of gadgets to increase the degree of myopia refractive error at the Ulak Karang Community Health Center in the city of Padang. This research uses quantitative descriptive methods. The population in this study were all purely optical patients in Padang City with a sample of all patients who experienced myopia caused by gadgets, namely 40 respondents. Data was collected through a questionnaire, then the data was discussed in accordance with the theory proposed in the literature review. The results of this research showed that the average frequency of respondents who answered the questionnaire items with the answer